Molecular Markers of Neuronal Progenitors in the Embryonic Cerebellar Anlage - Morales, Daniver (J Neurosci, 2006)
The cerebellum, like the cerebrum, includes a nuclear structure and an overlying cortical structure. Experiments in the past decade have expanded knowledge beyond the traditional function of the cerebellum to include critical roles in motor learning and memory and sensory discrimination. The initial steps in cerebellar development depend on inductive signaling involving FGF and Wnt proteins produced at the mesencephalic/metencephalic boundary. To address the issue of how individual cerebellar cell fates within the cerebellar territory are specified, we examined the expression of transcription factors, including mammalian homologues of LIM homeodomain-containing proteins, basic helix-loop-helix proteins, and three amino acid loop-containing proteins. The results of these studies show that combinatorial codes of transcription factors define precursors of the cerebellar nuclei, and both Purkinje cells and granule neurons of the cerebellar cortex. Examination of gene expression patterns in several hundred lines of Egfp-BAC (bacterial artificial chromosome) transgenic mice in the GENSAT Project revealed numerous genes with restricted expression in cerebellar progenitor populations, including genes specific for cerebellar nuclear precursors and Purkinje cell precursors. In addition, we identified patterns of gene expression that link granule and Purkinje cells to their precerebellar nuclei. These results identify molecular pathways that offer new insights on the development of the nuclear and cortical structures of the cerebellum, as well as components of the cerebellar circuitry.